War story - Jossen, Barry; Uno, Michael Toshiyuki; Guinee, Tim. (London : Odyssey Video, 1900)
The video contains six powerful real stories of Vietnam during the war
Tim Guinee ... (et al.)
Keywords: Vietnamese Conflict, 1961 -- 1975 -- Motion pictures and the conflict; War stories -- Drama